The Influence of Project Based Learning Model on Pancasila Education Learning Outcomes of Class IV of SD Negeri 96 Palembang: The Influence of Project Based Learning Model on Pancasila Education Learning Outcomes of Class IV of SD Negeri 96 Palembang - Eka Putri Alisya; Bambang Hermansah; Imelda Ratih Ayu (Global Action and Education for Society, 2025)
This research is motivated by the problem of low student learning outcomes below the KKTP of class IV in Pancasila Education Lessons. This is because students have difficulty in understanding the meaning of Pancasila values and students have not been able to apply Pancasila values in everyday life. So that an effective learning model is needed to improve student learning outcomes in Pancasila Education Lessons, namely the project based learning model. This study uses a quasi-experimental method with a one group pretest posttest design. The population in this study were all students of SD Negeri 96 Palembang, totaling 156 students consisting of 6 study groups, namely class one to class six. The sample used in this study was 20 students from class IV consisting of 12 boys and 8 girls. Data collection techniques in this study used tests, observations and documentation. The data analysis technique used in this study is the T test. Based on the results of the T test analysis, the t-test value> t table is 15.807> 2.093, which means that there is a significant difference between the pretest and posttest values and the sig value (2-tailed) 0.000<0.05 so that H0 is rejected. It can be concluded that the project based learning model has an effect on the learning outcomes of Pancasila Education in grade IV of SD Negeri 96 Palembang.